DEVELOPMENT OF PHISYICS LEARNING DOCUMENTS BASED STUDENT’S LEARNING STYLE IN THE MATTER OF TEMPERATURE AND HEAT SUBJECTS OF CLASS X HIGH SCHOOL - Resty Noriwita, Indah Resty Noriwita Indah; Nasir, Muhammad Nasir Muhammad; MaÃ¢Â€Â™aruf, Zuhdi MaÃ¢Â€Â™aruf Zuhdi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:This study aims to produce a learning documents physicsbased learning styles of students in the matter of temperature and heat of class subjectS X SMA valid. The subjects were learning documents that consists of a lesson plan (RPP), worksheets (LKS), medium of learning and achievement test of cognitive, affective, process, and psychomotor. Data collection instrument in this study is an instrument validity device physics-based learning students' learning styles in the matter of temperature and heat subjects of class X SMA. Data analysis in this study is a descriptive analysis of the scores by calculating the validity ofeachindicator validity of the learning documentss. Validity learning documents is determined by the score results of the validation by expert lecturers. Based on the results obtained by the validity of the RPP and LKS format at 100% with the higher category. RPP content validity of 84.14% with higher categories and content validity Worksheet 1, II, III and IV of 75.50% with a high category.rresults media validity of 87.24% with a higher category. Validity tests of cognitive learning outcomes of 84.50% with a higher category. The validity of the test results of the process of learning the skills of 80.19% with a higher category. Validity tests of psychomotor learning outcomes of 91.70% with a higher category. and validity of the test results of 100% affective learning with a higher category, so the learning documents is otherwise valid and ready for use as a learning documents in schools. KeyWords:Keywords: learning documents, learning styles, temperature and heat